Characterizing HIV risk among cisgender men in Latin America who report transgender women as sexual partners: HIV risk in Latin America men. (March 2019) - Reisner, Sari L; Perez-Brumer, Amaya; Oldenburg, Catherine E; Gamarel, Kristi E; Malone, Jowanna; Leung, Kingsley; Mimiaga, Matthew J; Rosenberger, Joshua G; Biello, Katie B.
Cisgender men (CM) who report transgender women (TW) as sexual partners are an understudied population in the HIV epidemic in Latin America. The current study sought to characterize this group in a 2012 cross-sectional online survey of Latin American CM who were members of a sexual networking website for men who have sex with men (N = 11, 847). Multivariable logistic regression models were fit to estimate demographic, behavioral, and psychosocial correlates of having a TW sexual partner and engaging in condomless sex. Overall, 0.9% (n = 106) reported a TW sexual partner in the last 12 months; of these, 76.4% (n = 81) reported condomless sex in the last three months. Identifying as bisexual or heterosexual compared to gay, and specifying a versatile sexual role preference compared to insertive were associated with reporting a recent TW sex partner (all p  < 0.05). HIV-negative serostatus, lifetime STI history, and alcohol dependence were associated with recent condomless sex (all p  < 0.05). CM with TW sexual partners have distinct HIV-related vulnerabilities. Future research is needed to understand CM who report TW sexual partners, including their sexual preferences and practices, sexual networks, exposure to stigma, biomedical prevention interest and uptake, and acceptability of integrating alcohol abuse screening into sexual health services.